2023
DOI: 10.1177/1476718x221145484
|View full text |Cite
|
Sign up to set email alerts
|

Researcher positionality in eliciting young children’s perspectives

Abstract: Research that uses innovative approaches to elicit the views of young children has grown hugely over the last 20 years. Against a backdrop of a greater acceptance of children’s rights and sociological approaches to understanding children and childhood, with their combined emphasis on the competences and capacities of children, it is now accepted that young children can be engaged with to seek their views, experiences and perspectives as part of research studies. The range of methodological approaches is extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In challenging the assumption that normative mathematical problem solving only develops in formal educational contexts, he observed that the skills children used in their street vending activities did not necessarily transfer to their school contexts and vice versa, and importantly, that children who were quite adept at using mathematics in their real-world vending activities were not necessarily able to translate their skills toward high-achievement on formal educational tasks (Saxe, 1988). Bilgen et al, 2021;Patton and Winter, 2023). 🟊 For example, Patton and Winter (2023) provide a detailed and reflexive account of researcher positionality and decision-making in engaging in an observational study with preschool-aged children.…”
Section: Considering Socio-cultural Contexts Of Problem Solvingmentioning
confidence: 99%
See 1 more Smart Citation
“…In challenging the assumption that normative mathematical problem solving only develops in formal educational contexts, he observed that the skills children used in their street vending activities did not necessarily transfer to their school contexts and vice versa, and importantly, that children who were quite adept at using mathematics in their real-world vending activities were not necessarily able to translate their skills toward high-achievement on formal educational tasks (Saxe, 1988). Bilgen et al, 2021;Patton and Winter, 2023). 🟊 For example, Patton and Winter (2023) provide a detailed and reflexive account of researcher positionality and decision-making in engaging in an observational study with preschool-aged children.…”
Section: Considering Socio-cultural Contexts Of Problem Solvingmentioning
confidence: 99%
“…Bilgen et al, 2021;Patton and Winter, 2023). 🟊 For example, Patton and Winter (2023) provide a detailed and reflexive account of researcher positionality and decision-making in engaging in an observational study with preschool-aged children. These researchers consider the use of a teddy bear named "Ted" as an elicitation tool for gathering information about children's perspectives and contextual experiences of early childhood educational settings.…”
Section: Considering Socio-cultural Contexts Of Problem Solvingmentioning
confidence: 99%